(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Distance and Virtual education have had a great development in university students, managing to meet their learning expectations without limitations of time and space, however, questions are raised such as: What are the reasons why they drop out of higher education students of online modalities? How could dropout in these modalities be currently reduced? To carry out this study, a systematic review under the PRISMA methodology was proposed as a method, and as results, individual, academic, socioeconomic, and institutional educational and administrative aspects that propose strategies such as interviews are among the most important reasons that influence dropout. and support for the entry of the modality, communication and rapid and effective feedback mediated by artificial intelligence, laboratories and virtual practices, financial aid, synchronous social and welfare activities that can be implemented from educational management and public policies.